Tissue response to collagen containing polypropylene meshes in an ovine vaginal repair model. (15th July 2016) - Darzi, Saeedeh; Urbankova, Iva; Su, Kai; White, Jacinta; Lo, Camden; Alexander, David; Werkmeister, Jerome A.; Gargett, Caroline E.; Deprest, Jan
Graphical abstract: Abstract: Pelvic Organ Prolapse (POP) is the herniation of pelvic organs into the vagina. Despite broad acceptance of mesh use in POP surgical repair, the complication rate is unacceptable. We hypothesized that collagen-containing polypropylene (PP) mesh types could modulate mesh-tissue integration and reduce long-term inflammation, thereby reducing mesh-associated complications. This study compared the long-term tissue response to an unmodified PP mesh and two collagen containing meshes in an ovine model which has similar pelvic anatomy and vaginal size to human. Three commercially available macroporous PP meshes, uncoated PP mesh (Avaulta Solo) (PP), the same textile PP mesh layered with a sheet of cross-linked porcine acellular matrix (Avaulta Plus) (PP-ACM) and a different yet also macroporous PP (Sofradim) mesh coated with solubilized atelocollagen (Ugytex) (PP-sCOL) were implanted in the ovine vagina and tissue explanted after 60 and 180 days. The macrophage phenotype and response to implanted meshes, and vascularity were quantified by immunostaining and morphometry. We quantified changes in extracellular matrix composition biochemically and collagen organisation and percentage area around the interface of the mesh implants by Sirius Red birefringence and morphometry. PP-ACM induced a more sustained inflammatory response, indicated by similar CD45 + leukocytes but reduced CD163 + M2 macrophages at 60 days (P < 0.05). PP-sCOL increased Von Willebrand Factor (vWF)-immunoreactive vessel profiles after 60 days. At the micro-molecular level, collagen birefringence quantification revealed significantly fewer mature collagen fibrils (red, thick fibrils) at the mesh-tissue interface than control tissue for all mesh types (P < 0.001) but still significantly greater than the proportion of immature (green thin fibrils) at 60 days (P < 0.05). The proportion of mature collagen fibrils increased with time around the mesh filaments, particularly those containing collagen. The total collagen percent area at the mesh interface was greatest around the PP-ACM mesh at 60 days (P < 0.05). By 180 days the total mature and immature collagen fibres at the interface of the mesh filaments resembled that of native tissue. In particular, these results suggest that both meshes containing collagen evoke different types of tissue responses at different times during the healing response yet both ultimately lead to physiological tissue formation approaching that of normal tissue. Statement of Significance: Pelvic organ prolapse (POP) is the descent of the pelvic organs to the vagina. POP affects more than 25% of all women and the lifetime risk of undergoing POP surgery is 19%. Although synthetic polypropylene (PP) meshes have improved the outcome of the surgical treatment for POP, there was an unacceptable rate of adverse events including mesh exposure and contracture. It is hypothesized that coating the PP meshes with collagen would provide a protective effect by preventing severe mesh adhesions to the wound, resulting in a better controlled initial inflammatory response, and diminished risk of exposure. In this study we assessed the effect of two collagen-containing PP meshes on the long-term vaginal tissue response using new techniques to quantify these tissue responses.